The Edible garden urban agriculture in Metro Manila - Morales-Sundiang, Cynthia 1963- (College of Architecture, University of the Philippines, Diliman, 1995)
It aims to lay the goundwork for a more comprehensive study and an inderdisciplingay appoach towards a successful Urban Agriculture Programme in Metro Manila.